Bidding strategies and takeover premiums: A review - Eckbo, B. Espen (Journal of Corporate Finance, 2009)
I review recent empirical research documenting offer premiums and bidding strategies in corporate takeovers. The discussion ranges from optimal auction bidding to the choice of deal payment form and premium effects of poison pills. The evidence describes the takeover process at a detailed level, from initial premiums to bid jumps, entry of rival bidders, and toehold strategies. Cross-sectional tests illuminate whether bidders properly adjust for winner's curse, whether target stock price runups force offer price markups, and whether auctions of bankrupt firms result in fire-sale discounts. The evidence is suggestive of rational strategic bidding behavior in specific contexts.